NOTE ON THE FETUSES OF THE DOLPHINS TURSIOPS ADUNCUS AND SOUSA PLUMBEA FROM THE SOUTH WEST COAST OF INDIA - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Though our knowledge of the distribution and occurance of dolphins along the Indian coaist is faidy good (Blanfond 1891), iirformation on their reproductive biol<^y is very meagre. Whffle studying the dolphins of southwest coast of India during 1976-1981, two fetuses of the bottlenose dolphin Tursiops odurKus and one fetus of Che humpback dolphin Sousa plumbea were examined The observations made on ftem ame presented here.